Exploring the use of films/dramas in giving awareness towards mental illness in society - Nor Mazlina Ghazali; Edris Aden; Azzahrah Anuar; Fatahyah Yahya; Anis Natasha Zulkifli (International Journal of Public Health Science (IJPHS), 2021)
This study was exploring the use of films/dramas in giving awareness towards mental illness among society. Objective of this study was to explore the use of films in giving awareness on mental illness to the community. The study used qualitative research design. There were 11 participants of this study which consisted of three stages of human development (adolescent, early and late adulthood). They also come from varies background such as different work setting, age, occupation as well as level of education. The varies background among participants were provided different answers of questions. The method of data collection was an interview with semi-structured questions. Analysis of data using Thematic Analysis. Findings showed few themes have been found from the interview such as personality of participants that lead them to watch this type of films/dramas, effect after they watched this type of films/dramas, perception of participants towards mental illness films/dramas, learning process and suggestion to improve this type of films/dramas in Malaysia. The implication of this study, participants gaining more awareness on mental illness after watching type of films/dramas. They also found this genre of films/dramas enable to educate them to be open with people who suffer from mental illness. In conclusion, future researcher can explore the effect of watching mental illness genre films/dramas towards self-development among society.